2018
DOI: 10.1520/acem20170104
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and Economic Impacts of Using Asphalt Rubber Mixtures at Various Vehicle Speeds

Abstract: In the application of hot-mix asphalt pavement (HMA), tension at the bottom of the HMA layer creates one of the most challenging distresses to pavement structures, fatigue cracking. Adding rubber to the asphalt mix can extend the life of a pavement and provide an end use for old tires that would otherwise end up in a landfill. It is already known that the initial construction cost of an asphalt rubber mix will be higher than that of a conventional mix. However, the purpose of this article is to investigate if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…where the N f is the fatigue life, which can be expressed by Equation ( 12): 12) can be transformed into Equation (13).…”
Section: Phenomenological Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where the N f is the fatigue life, which can be expressed by Equation ( 12): 12) can be transformed into Equation (13).…”
Section: Phenomenological Methodsmentioning
confidence: 99%
“…Most of the design methods of asphalt pavement structures in the world use the mechanics-experience method, which uses mechanical methods to calculate the load response of the pavement structure. It uses homogeneous and isotropic linear elastic mechanics as the mechanical model for structural response calculation [ 9 , 10 , 11 , 12 , 13 ]. The strength, stiffness, and fatigue parameters are essential parameters in calculating the load response and establishing the mechanical model, which plays a vital role in the design of the pavement structure.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have proven the economic advantage of adding tires to asphalt binders since recycled tires markedly reduce the need for using new materials [16]. The use of waste materials for asphalt stabilisation is regarded as a smart strategy for sustainable development.…”
Section: Figure 1 the Waste Hierarchy For Pavement Materials [15]mentioning
confidence: 99%
“…Furthermore, the crushed concrete in several types of research confirmed that the recycled concrete aggregates (RCA) are applicable for reuse on the roads, concrete pavement when it is replaced with a proper percentage of new aggregate [11][12][13][14]. The use of recycled materials as an eco-friendly substitute has performance, economic and environmental benefits [15,16]. Figure 1 shows the waste hierarchy applied to pavement materials.…”
Section: Introductionmentioning
confidence: 99%